Characterization of microbial community and antibiotic resistome in intra urban water, Wenzhou China - Ye, Sheng; Li, Shengkai; Su, Chenjun; Shi, Zhuqing; Li, Heng; Hong, Jiawen; Wang, Shengke; Zhao, Jingyan; Zheng, Weiji; Dong, Shixuan; Ye, Shuhan; Lou, Yongliang; et al. (Frontiers in Microbiology, 2023)
The present study investigated the water quality index, microbial composition and antimicrobial resistance genes in urban water habitats. Combined chemicals testing, metagenomic analyses and qualitative PCR (qPCR) were conducted on 20 locations, including rivers from hospital surrounds (n = 7), community surrounds (n = 7), and natural wetlands (n = 6). Results showed that the indexes of total nitrogen, phosphorus, and ammonia nitrogen of hospital waters were 2–3 folds high than that of water from wetlands. Bioinformatics analysis revealed a total of 1,594 bacterial species from 479 genera from the three groups of water samples. The hospital-related samples had the greatest number of unique genera, followed by those from wetlands and communities. The hospital-related samples contained a large number of bacteria associated with the gut microbiome, including Alistipes, Prevotella, Klebsiella, Escherichia, Bacteroides, and Faecalibacterium, which were all significantly enriched compared to samples from the wetlands. Nevertheless, the wetland waters enriched bacteria from Nanopelagicus, Mycolicibacterium and Gemmatimonas, which are typically associated with aquatic environments. The presence of antimicrobial resistance genes (ARGs) that were associated with different species origins in each water sample was observed. The majority of ARGs from hospital-related samples were carried by bacteria from Acinetobacter, Aeromonas and various genera from Enterobacteriaceae, which each was associated with multiple ARGs. In contrast, the ARGs that were exclusively in samples from communities and wetlands were carried by species that encoded only 1 to 2 ARGs each and were not normally associated with human infections. The qPCR showed that water samples of hospital surrounds had higher concentrations of intI1 and antimicrobial resistance genes such as tetA, ermA, ermB, qnrB, sul1, sul2 and other beta-lactam genes. Further genes of functional metabolism reported that the enrichment of genes associated with the degradation/utilization of nitrate and organic phosphodiester were detected in water samples around hospitals and communities compared to those from wetlands. Finally, correlations between the water quality indicators and the number of ARGs were evaluated. The presence of total nitrogen, phosphorus, and ammonia nitrogen were significantly correlated with the presence of ermA and sul1. Furthermore, intI1 exhibited a significant correlation with ermB, sul1, and blaSHV, indicating a prevalence of ARGs in urban water environments might be due to the integron intI1’s diffusion-promoting effect. However, the high abundance of ARGs was limited to the waters around the hospital, and we did not observe the geographical transfer of ARGs along with the river flow. This may be related to water purifying capacity of natural riverine wetlands. Taken together, continued surveillance is required to assess the risk of bacterial horizontal transmission and its potential impact on public health in the current region.